Safety First: The Role of Safety Climate as a Predictor of Safety Behavior Through Safety Knowledge as a Mediating Variable - maryati, Maryati; Hakim, Arif Rahman; Maulidia, Ananda Saadatul (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Companies must prioritize work safety as the main thing to create a safe and healthy work environment. The research conducted has the aim of knowing the role of safety climate as a predictor of safety behavior through safety knowledge as a mediating variable. The method used is a convenient sampling technique. The number of respondents was 154 workers. The research instrument used a safety behavior scale created by Neal and Griffin, safety climate measured using (LSCAT) compiled by Cox and Cheyne, safety knowledge scale compiled by Vinodkumar and Bhasi. To analyze the data using classical assumptions, namely, Kolmogorov-smirnov normality test, linearity test and heteroscedasticity test and hypothesis testing, namely mediation regression analysis technique. The results of the direct effects test of the safety climate variable on safety behavior show a significant effect with a significance level of 0.006 which indicates a significant influence between safety climate and safety behavior, besides that the indirect effects between safety climate and safety behavior through mediation of safety knowledge have a significance level of 0.004, meaning that there is a mediating role between safety climate and safety behavior through safety knowledge. PT X is expected to maintain and improve safety behavior with a safety climate that supports the work safety program and can also design a more effective safety training program that suits the needs of workers.Perusahaan harus memprioritaskan keselamatan kerja sebagai hal utama untuk menciptakan lingkungan kerja yang aman dan sehat. Penelitian yang dilakukan ini memiliki tujuan untuk mengetahui peran safety climate sebagai prediktor safety behavior melalui safety knowledge sebagai variabel mediasi. Metode yang digunakan yaitu teknik convenient sampling. Jumlah responden sebanyak 154 pekerja. Instrumen penelitian menggunakan safety behavior scale yang dibuat oleh Neal dan Griffin, safety climate diukur dengan menggunakan (LSCAT) yang disusun oleh Cox dan Cheyne, skala safety knowledge yang disusun oleh Vinodkumar dan Bhasi. Untuk menganalisis data menggunakan asumsi klasik yaitu, uji normalitas Kolmogorov-smirnov, uji linearlitas dan uji heteroskedastisitas serta uji hipotesis yaitu teknik mediation regression analysis. Hasil uji direct effects variabel safety climate terhadap safety behavior menunjukan pengaruh yang signifikan dengan taraf siginifikansi 0,006 yang menunjukan adanya pengaruh signifikan antara safety climate dengan safety behavior, selain itu pengaruh indirect effects antara safety climate dan safety behavior melalui mediasi safety knowledge memiliki taraf signifikansi sebesar 0.004 artinya ada peran mediasi antara safety climate dengan safety behavior melalui safety knowledge. PT X diharapkan dapat mempertahankan serta meningkatkan perilaku keselamatan (safety behavior) dengan iklim keselamatan (safety climate) yang mendukung program keselamatan kerja, selain itu juga dapat merancang proram pelatihan keselamatan kerja yang lebih efektif yang sesuai dengan kebutuhan pekerja.